ANALYSYS OF PUBLIC VALUE IN THE ENTREPRENEURSHIP TRAINING PROGRAM AT LAPAS KELAS IIA BOJONEGORO - Rembran Mardika Resepta Naba; Esa Septian; Sri Kasiami (Journal of Social Politics and Governance (JSPG), 2026)
-